Global trends and forecasts of nonalcoholic steatohepatitis causing liver cancer incidence and deaths - Cui, Tao; Guan, Chenyue; Song, Kun; Yu, Jiangtao (Frontiers in Oncology, 2026)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD), particularly its progressive form, nonalcoholic steatohepatitis (NASH), has emerged as a leading cause of hepatocellular carcinoma (HCC). The burden of MASLD is increasing rapidly in parallel with the rising global prevalence of obesity and metabolic syndrome, affecting approximately 30% of the world’s population.ObjectiveThis study aimed to quantify global trends in NASH-related liver cancer incidence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021 and to project the future disease burden through 2035.MethodsData from the Global Burden of Disease Study 2021, encompassing 204 countries, were utilized to evaluate age-standardized incidence (ASIR), mortality (ASMR), and DALY rates (ASDR) across 21 regions and five Socio-demographic Index (SDI) categories, with stratification by age, sex, and geographical location. Future trends were projected using statistical modeling approaches, while decomposition analysis was employed to identify the key drivers of changes in disease burden.ResultsFrom 1990 to 2021, global ASIR of NASH-related HCC increased by 25% (0.4-0.5 per 100,000), with an EAPC of +3.5% (95% UI: 3.4-3.6). ASMR rose by 150% (0.2-0.5 per 100,000; EAPC + 3.2%), and ASDR increased by 20% (9.6-11.5 per 100,000; EAPC + 2.9%).Regional disparities: Australasia saw the steepest rise (ASIR + 200%, EAPC + 7.2%; ASMR + 150%, EAPC + 6.9%). High-income North America followed (ASIR + 160%, EAPC + 5.3%).Age/sex differences: Incidence peaked in ages 85–89 (6.31 per 100,000 men; 5.56 per 100,000 women). Men had higher burden, for example, 55–59 years: male ASIR 1.28 vs. female 0.87 per 100,000. but gender gaps narrowed after age 75.Risk drivers: Metabolic factors such as high fasting glucose accounted for 29.7% of deaths in ages 80–84; smoking contributed 11.1% in ages 55–59.Projections: By 2035, ASIR will rise to 0.74 per 100,000 (+7% from 2021), driven by aging, population growth, and epidemiological changes (52% of incidence increase globally).ConclusionNASH-related HCC burden exhibits accelerating global growth, concentrated in high-SDI regions. Prioritizing metabolic management and early screening is critical to mitigate future burden.